Egalitarian myths in New Zealand: a review of public opinion data on inequality and redistribution - Skilling, PD (New Zealand Sociology, 2013)
Economic inequality in developed western countries, including New Zealand, is a pressing social issue. Besides concerns of fairness, current high levels of inequality are associated with a range of socially damaging consequences. Drawing on new and existing data, this article presents a summary and an analysis of New Zealanders’ beliefs about economic inequality and political redistribution. It explicates and explores some apparent puzzles and paradoxes within the data, including the divergence found between respondents’ (declining, but still substantial) level of concern about economic inequality and their (much more limited) support for specific measures that would reduce that inequality. The article discusses some key factors that appear to influence opinion on inequality and redistribution, and it concludes with suggestions for future research to further explore some of the puzzles within the existing data.
Keywords: Economics--political aspects; Income distribution--public opinion; Questionnaires--methodology; Cost and standard of living